Menggunakan Seesaw untuk Kelas 3 SD Desain Proyek Pembelajaran Kolaboratif "Pentingnya Menjaga Kebersihan Lingkungan" Dengan Dokumentasi Seesaw untuk Kelas 3 SD - Ludya Fatmawati; Ika PutraViratama (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2026)
The use of digital technology in elementary school learning has become an essential requirement in line with the development of 21st-century education. One platform that can be utilized is Seesaw, a digital portfolio application that allows students to document and reflect on their learning processes collaboratively. This study aims to describe the design of a collaborative project-based learning activity entitled “The Importance of Maintaining Environmental Cleanliness” using Seesaw for third-grade elementary school students and to analyze the outcomes of its implementation in the learning process.This research employed a qualitative descriptive approach with third-grade elementary school students as the research subjects. Data collection techniques included classroom observations, documentation of students’ project work uploaded on Seesaw, and teacher interviews. The results indicate that the use of Seesaw in collaborative project-based learning enhances student engagement, group cooperation, and students’ awareness of the importance of maintaining environmental cleanliness. In addition, Seesaw facilitates teachers in documenting learning activities and conducting authentic assessments. Therefore, Seesaw can be considered an effective learning medium to support thematic, project-based learning in elementary schools.